Trends on virtualisation with software defined networking and network function virtualisation. Issue 5 (1st September 2015) - Barona López, Lorena Isabel; Valdivieso Caraguay, Ángel Leonardo; García Villalba, Luis Javier; López, Diego
Abstract : Software defined networking (SDN) and network function virtualisation (NFV) have become hot topics in recent years. On one hand, SDN decouples the control plane from the data plane allowing the rapid innovation and the introduction of new services in an easy way. On the other hand, currently proprietary appliances such as load balancers and firewalls are implemented in hardware, NFV aims to change these network functions to an open software environment using virtualisation and cloud technologies. This means a reduction of spends in the provisioning and management of telecom services. SDN and NFV are two different concepts but these can coexist and help each other. In this study, the authors present a survey of SDN and NFV focusing in virtualisation projects and the use cases where a synergy between these technologies is possible. This study includes the basic concepts of network virtualisation, NFV and SDN, current research and the relation between both technologies.